Criminal Act of Misuse of Patient Medical Data Against Health Insurance - Sukaina Aziilah; Muhammad Fauzi Ramadhan; Tri Abriana Ma'ruf (HORIZON PUBLIC LEGAL STUDIES, 2025)
This study This study aims to analyze the criminal misuse of patient medical data in the context of health insurance in Indonesia, which is a crucial issue in protecting individual privacy rights. In practice, misuse of medical data is not uncommon, both directly and indirectly, which can harm patients physically, psychologically, and financially. This study uses a normative juridical approach by examining the applicable legal framework, combined with case studies as an empirical approach to assess how the law is implemented in the field. The results show that although a legal framework governing medical data protection exists, its implementation still faces various challenges, such as weak oversight, low legal literacy among data holders, and the absence of a firm and effective sanction mechanism. This study provides several strategic recommendations to strengthen legal protection for patient medical data, including through regulatory harmonization, increased oversight, education for stakeholders, and the establishment of an independent supervisory body authorized to protect personal data in the health and insurance sectors.